Resolving developmental conflict in Africa through bilateral relationship with Asian countries - Halliru, Tijjani; Ibrahim, Yahya Saleh (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
Bilateral relationship has the potentiality of changing the economic posture and prospect of the African economy. It has the potentiality of resolving the African ethno-religious and communal conflict as well serve as an instrument to galvanize all the abundant resources in Africa and transform them into the nucleus that can bring about socio-economic and political development, create employment opportunities and national integration. This bilateral relationship especially with Asia has a long historical record in Africa specifically with Nigeria, during the regime of late General Murtala Muhammad 1975-1976, the General Muhammad Buhari/Idiagbon regime 1983-1985, General Muhammad Sani Abacha Administration 1993-1998, and of recent the attempt made by the present administration of Alhaji Umaru Musa Yaradua/Goodluck 2007 to date for shifting the economic policy to the Asian continent in search of Nigerian solution to the ailing economy, and the resultant conflict that served as one factor sustaining Nigeria economic instability. This paper is based on deductive, inductive and comparative methods of research which specifically concludes that, it is possible for bilateral relationship with Asian countries, particularly Malaysia, Thailand and Singapore to serve as a platform for resolving ethno-religious conflict and economic instability, an attempt as stated above prove to be very useful as reflected in the history of Nigeria.